Integrasi Alkitab Pada Strategi Coping Albert Ellis: Masukan Bagi Konseling Kristen Penderita Depresi - Siwabessy, Donald (SAINT PAUL'S REVIEW, 2023)
Handling of the problem of depression which continues to increase after the Covid Pandemic, can be handled through Christian counseling using Albert Ellis's coping strategy approach. This study aims to integrate Bible truth into Albert Ellis's coping strategies, which are inputs for treating depression through Christian counseling. This study used a qualitative research method with a literature study approach. The results of the study show that the integration of the Bible into Albert Ellis's coping strategies can be carried out carefully, by eliminating aspects that are not in line with Bible truths, and accommodating aspects that are in line with the Bible to then be integrated into the coping strategy. Through this process the integration of the Bible into Albert Ellis's coping strategies can be an important input for treating depression through Christian counseling.